A Case Report of Hematuria in Heparin-Induced Thrombocytopenia: An Unusual Presentation Leading to End Organ Damage - Mansoor Abbas Qaiser, Mansoor Abbas Qaiser (Journal of Rawalpindi Medical College, 2020)
Heparin‐induced thrombocytopenia (HIT) is a potential devastating complication of heparin therapy. It is an immunoresponse in which platelet activation is caused by antibodies. HIT is associated with both arterial and venous thromboembolism and regardless of thrombocytopenia, bleeding is rare presentation. Here, we present a case of HIT where patient initially presented with frank hematuria but later developed thrombosis and ultimately developed infarction of the kidney due to renal vein thrombosis.